Effect of ageing process on mechanical properties of adhesive tubular butt joints in aqueous environment. (January 2020) - Rudawska, Anna; Abdel Wahab, Magd; Müller, Miroslav
Abstract: We present, for the first time, an original experimental study on the effect of ageing process (seasoned in the aqueous environment) on the mechanical behaviour of adhesive tubular butt joints. In order to manufacture adhesive tubular butt joints, tubes with a diameter of 20 ± 1 mm, made of three different materials (polypropylene, carbon steel and galvanised steel) were considered. Two types of the adhesive epoxy compounds were used, namely a flexible adhesive (Epidian 57/PAC/100:80) and a stiff adhesive (Epidian 57/Z1/100:10). The ageing process, including the adhesive joint samples' seasoning in a specific environment, was conducted using three aqueous environments, namely mineral water, demineralised water and supply water. The specimens were aged for 3 months and 6 months. In addition, one reference sample subjected to the ageing process was considered. After ageing, the samples were subjected to tensile strength tests. These tests were carried out using the ZWICK/ROELL Z150 testing machine in accordance with the norm EN 15870. Based on the test results' analysis, it was observed that the longer the seasoning time of the adhesive joint samples, the more negative effects on the adhesive joints (decreased strength regardless of the adhesive type or the material). For tubes made of both galvanised and carbon steel, the joints could work well in short-term exploitation as they would keep their strength for a certain period. Such joints could be less expensive in short-term exploitation than the widely used mechanical joints.